Iron nanoparticles mitigate cadmium-induced abiotic stress in soybean by modulating reactive oxygen species accumulation and cellular integrity - Mukhtar, Ahmed; Jabeen, Shaista; Asad, Muhammad Shoaib; Jaffar, Muhammad Tauseef; Abdel-Maksoud, Mostafa A.; Alrokayan, Salman; Chen, Xiaoli; Ren, Xiaolong (Frontiers in Plant Science, 2026)
Cadmium (Cd) is a toxic heavy metal that causes morphological and physiological changes to plants, which eventually leads to a decline in growth and productivity. Nanoparticle-based amelioration of Cd toxicity in plants is an environmentally friendly and cost-effective approach. Nevertheless, the interaction between iron nanoparticles (FeNPs) and Cd in soybean (Glycine max L.) is still not well documented. This research was conducted to evaluate the effects of soil application of FeNPs on soybean plants exposed to Cd stress. The size, surface morphology, and crystalline nature of the FeNPs were observed using scanning electron microscopy (SEM) and X-ray diffraction (XRD). Soil amended with FeNPs (50 mg L−1) decreased reactive oxygen species (ROS) accumulation and improved photosynthetic performance in comparison with Cd treatment (40 mg kg−1). These enhancements of peak fluorescence (Fp), maximum potential efficiency of photosystem II (Fv/Fm), photochemical quenching (Qp), and fluorescence decrease ratio (Rfd) were positively correlated with leaf stomatal opening and growth, while negatively correlated with non-photochemical quenching (NPQ), H2O2, and O2·− content. Subcellular localization via transmission electron microscopy analysis showed that the FeNPs improved the intracellular integrity with the development of key cellular organelles and active Cd sequestration in plant vacuoles. Furthermore, FeNPs inhibited oxidative stress by 34%–56% via the modulation of antioxidant enzymes, i.e., superoxide dismutase (SOD), peroxidase (POD), glutathione (GSH), ascorbic acid (AsA), catalase (CAT), and reductase activity. Overall, FeNPs serve as a potent ameliorative agent against Cd-induced phytotoxicity by enhancing antioxidant defense mechanisms, optimizing photosynthetic performance, preserving cellular integrity, and significantly suppressing oxidative stress.